A systematic review and meta‐analysis of behavioural sex differences in executive control. (10th September 2020) - Gaillard, Alexandra; Fehring, Daniel J.; Rossell, Susan L.
Abstract: Literature investigating whether an individuals' sex affects their executive control abilities and performance on cognitive tasks in a normative population has been contradictory and inconclusive. Using meta‐analytic procedures (abiding by PRISMA guidelines), this study attempts to identify the magnitude of behavioural sex differences in three prominent executive control domains of cognitive set‐shifting, performance monitoring, and response inhibition. PubMed, Web of Science, and Scopus were systematically searched. Across 46 included studies, a total of 1988 females and 1884 males were included in the analysis. Overall, males and females did not differ on performance in any of the three domains of performance monitoring, response inhibition, or cognitive set‐shifting. Task‐specific sex differences were observed in the domains of performance monitoring, in the CANTAB Spatial Working Memory task—males scored statistically higher than females (Hedges' g = −0.60), and response inhibition, in the Delay Discounting task—females scored statistically higher than males (Hedges' g = 0.64). While the meta‐analysis did not detect overall behavioural sex differences in executive control, significant heterogeneity and task‐specific sex differences were found. To further understand sex differences within these specific tasks and domains, future research must better control for age and sex hormone levels. Abstract : Due to inconsistencies within the literature, we conducted a meta‐analysis on sex differences in executive control. Here, we show that males and females do not differ in the executive control domains of performance monitoring, response inhibition, and cognitive set‐shifting. However, there are task‐specific differences observed on the CANTAB spatial working memory task and the delay discounting task. Our results indicate a need for more well‐controlled studies to understand how sex differences may influence task performance.